Responding to Failure: A Transformative Process - Davey, Dean (Christian education journal, 2022)
Failure is the pathway to transformation. Employing reflective strategies within the three primary domains of knowledge enhances the learning process amidst failure. Where the suffering of failure can seem traumatic, systematic reflection enables learners to comprehensively analyze their behavior and evaluate its contribution to performance outcomes, resulting in posttraumatic growth and transformative results. Failure, of any kind, need not have the final word.